Increase of structural defects by N doping in MoS2 cross-linked with N-doped CNTs/carbon for enhancing charge transfer in oxygen reduction. (1st September 2018) - Yang, Liu; Cai, Zhuang; Hao, Liang; Ran, Lingling; Xu, Xin; Dai, Ying; Pan, Siyu; Jing, Baojian; Zou, Jinlong
Abstract: To improve the sluggish kinetics of oxygen reduction reaction (ORR) is critically important for the development of fuel cells. It is generally recognized that catalysts with multi-transfer channels and varied active sites can energetically facilitate the ORR-relevant species transfer to improve the oxygen reduction rate. In this study, N-doped carbon nanotubes-crossed MoS2 /carbon (N-MoS2 /CNTs/C) catalysts are synthesized at temperatures of 600–900 °C using an in-situ reduction self-assembly method. In both acid (0.5 M H2 SO4 ) and alkaline (0.1 M KOH) media, N-MoS2 /CNTs/C (800 °C) catalyst exhibits a promising ORR activity and favors a four-electron reduction pathway. The highly-maintained tubular CNTs in N-MoS2 /CNTs/C (800 °C) can supply the multidimensional pathways for transferring the ORR-relevant species. N atoms doping can not only increase the structural defects of MoS2 lattice (Mo–Nx ) to expose more Mo–Sx sites, but also induce various N functional groups into the carbon matrix (CNTs and porous carbon), which are favorable to improve the activation, adsorption and reduction of oxygen. Therefore, the distinct structures endow the N-MoS2 /CNTs/C catalysts with high activity towards ORR. Furthermore, the N-MoS2 /CNTs/C (800 °C) also exhibits a promising ORR activity in neutral medium (microbial fuel cells (MFCs)). MFCs with the N-MoS2 /CNTs/C (800 °C) cathode exhibits the maximum power density of 987.4 mW m −2, which is much higher than that of commercial Pt/C (601.96 mW m −2 ). These results indicate that N-MoS2 /CNTs/C catalysts can be considered as a promising alternative to Pt/C for ORR. Graphical abstract: Image 1 Highlights: Highly-maintained tubular CNTs in N-MoS2 /CNTs/C enhance the electron transfer. Varied active sites induced by N-doping promote oxygen adsorption and reduction. N-doping increases MoS2 structural defects (Mo–Nx ) to expose more Mo–Sx sites. N- MoS2 /CNTs/C catalyst exhibits promising ORR activity in acid and alkaline media. MFCs with N-MoS2 /CNTs/C (800 °C) cathode exhibits higher performance than Pt/C.